KETAHANAN KELUARGA SEBAGAI PILAR PEMBANGUNAN (ANALISIS KUALITATIF MENGGUNAKAN NVIVO ) - Santosa, Agus Djoko; Lastariwati, Badraningsih; Sovitriana, Rilla; Nilawati, Evi; Trisnawati, Nana (IKRA-ITH ABDIMAS, 2020)
Family development becomes an integral part of national development, with anemphasis on strengthening family resilience, noting that family resilience, having areciprocal relationship with poverty, is very significant, the lower the poverty rate or povertyindex in a low region , it will projectively increase economic security, social security, andphysical security. Handling family resilience at the community level, is a government priorityStudy of family resilience in the locus has the aim of accelerating the development andincreasing community appreciation of family resilience, with a qualitative analysis approach,data collection is done with focus groups, and followed by the PRA model, so that,Involvement of researchers in research with informants at the locus level Qualitative analysismethods with the help of Nvivo, the results show that resilience at the family level in generalstill needs to be improved by increasing physical, social, economic, cultural andenvironmental indicators, which portray the functions of government and societysimultaneously.